An investigation of the microstructural effects on the mechanical and electrochemical properties of a friction stir processed equiatomic CrMnFeCoNi high entropy alloy. (10th October 2021) - Anaman, Sam Yaw; Ansah, Solomon; Cho, Hoon-Hwe; Jo, Min-Gu; Suh, Jin-Yoo; Kang, Minjung; Lee, Jong-Sook; Hong, Sung-Tae; Han, Heung Nam
Graphical abstract: Highlights: FSPed CrMnFeCoNi HEA is studied in aerated 0.5 M Na2 SO4 at room temperature. Experimental, theoretical, and numerical approaches are implemented in this study. Grain refinement increases the corrosion resistance of the FSPed HEA. Micro-galvanic effect contributes to the pitting behavior of the FSPed HEA. Model can track the dissolution in the pits over longer periods during corrosion. Abstract: The electrochemical properties of a friction stir processed (FSPed) equiatomic CrMnFeCoNi high-entropy alloy (HEA) was investigated in an aerated 0.5 M Na2 SO4 electrolyte solution at room temperature. The microstructural analysis reveals a highly refined stir zone (SZ) with an average grain size that decreases from the top region of the SZ to the bottom region of the SZ (also known as shear-processed zone; SPZ). However, the region below the SPZ, (i.e. below the plunge depth) experienced an increase in average grain size and dislocation densities compared to the other regions. There is no secondary phase observed in the FSPed region, however, the microstructural evolution in the FSPed region affects the electrochemical behavior of the HEA. Cr2 O3 passive layer was observed to form on the FSPed HEA, leading to excellent corrosion properties from the polarization corrosion tests. Grain refinement in the SZ enhances the rapid formation of the passive layer, thus, leading to better corrosion properties in the front surface of the FSPed HEA. The localized corrosion behavior of the FSPed HEA was predicted to be caused by the micro-galvanic nature of the HEA, which leads to an increase in polarization at the anodic sites (pits). A numerical model was established using the corrosion parameters from the experiment to simulate the localized corrosion behavior on the surface of the FSPed HEA in a neutral environment. The predicted initial pitting potential and corresponding current density agree well with the experimental results. The model is also capable of tracking the dissolution of the pits over longer periods.